"It's been up and down"—perspectives on living through COVID-19 for individuals who experience homelessness: a qualitative study. (November 2021) - Adams, Emma A; Parker, Jeff; Jablonski, Tony; Kennedy, Joanne; Hunter, Desmond; Tasker, Fiona; Smiles, Claire; Muir, Cassey; Widnall, Emily; Dotsikas, Kate; Reed, Chris; Burrows, Martin; et al.
Abstract: Background: The UN describes the COVID-19 pandemic as the greatest public health crisis for the current generation. However, individuals who experienced austerity, adversity, and disadvantage prior to the pandemic have been disproportionately affected with every turn the pandemic has taken, from transmission risk to vaccination take-up. One such population is individuals who experience homelessness. As the UK begins to transition to a stage of post-pandemic recovery, it is imperative to understand the perceived impact COVID-19 has had on the day-to-day lives of individuals who experience homelessness, to ensure they are not left behind and recovery planning can be better targeted to their specific needs. Methods: Between February and May, 2021, 26 individuals (10 women and 16 men) who self-identified as experiencing homelessness within the Newcastle Gateshead area took part in telephone interviews of 20–80 min in length. Participants provided written or verbal informed consent prior to participating. Recruitment took place through existing networks, housing providers, charities, word of mouth, and snowball sampling. Analysis was co-produced with five individuals with lived experience using interpretative phenomenological analysis. NVivo release 1·5 was used to organise quotes. Ethics approval was granted by the Faculty of Medical Sciences Research Ethics Committee, part of Newcastle University's Research Ethics Committee (ref 2034/6698/2020.) Findings: Experiences shared depicted unique stories with commonalities across the findings through five main themes: (1) surreality of day-to-day life—searching for understanding and lost autonomy; (2) an emotional rollercoaster—confronting negative emotions; (3) loneliness is my best friend—learning from being alone; (4) adversity is the only consistency—recognising past and present hardship, violence, and loss; and (5) coping with uncertainty—using drugs, mindfulness, and technology to survive. Interpretation: The pandemic has affected the daily lives of people who experience homelessness in a variety of ways, including personal growth, no change, and regression. This study is limited by its localised recruitment in Newcastle and Gateshead in the UK; however, this local focus and involvement of individuals with lived experience has strengthened the study's implications for policy and practice in the region. Initiatives or policies developed to support post-pandemic recovery should reflect the array of impacts, while giving special recognition to loneliness, adversity, and resiliency among individuals who experience homelessness. Funding: National Institute for Health Research School for Public Health Research.